Evaluation of compensatory gain, standardized ileal digestible lysine requirement, and replacing specialty protein sources with crystalline amino acids on growth performance of nursery pigs. - Nemechek, Jeremiah Eugene (Kansas State University, 2011)
A total of 5,212 nursery pigs were used in 11 experiments to evaluate amino acids in nursery pig diets. Experiments 1 and 2 were conducted to determine whether the Lys level fed during one phase of the nursery influenced the response to Lys during subsequent phases. Experiment 1 tested a wide range of dietary Lys in 2 phases and reported that pigs fed high Lys during each period had increased growth performance; however, compensatory growth occurred for the pigs previously fed low Lys diets, resulting in no impact on overall ADG or final BW. Experiment 2 tested a narrow range of dietary Lys in 3 phases and found that marginally deficient diets can be fed in the early nursery phases without influencing final BW or the response to Lys levels in subsequent phases. Both experiments demonstrate that the low dietary Lys levels used in each can be fed in the early nursery phases with no negative impact on overall nursery growth rate provided that adequate levels are fed thereafter. Experiments 3 to 6 were conducted to determine the standardized ileal digestible (SID) Lys requirement of nursery pigs from 7- to 14-kg. Data from all experiments were combined and break-point and quadratic broken-line analysis was used to determine the estimated SID Lys requirement. The SID Lys requirement for optimal growth was at least 1.30% for ADG and 1.37% for G:F, or at least 3.86 and 4.19 g SID Lys/Mcal ME, respectively. Experiments 7 to 11 were conducted to evaluate the effect of replacing specialty protein sources with crystalline AA and AA requirements for 7- to 12-kg pigs. Experiment 7 demonstrated that crystalline AA can be used to replace fish meal in diets with no negative effects on growth performance. Experiment 8 demonstrated that L-Trp, L-Val, and a source of non-essential AA were needed in low-CP, AA-fortified nursery diets to achieve maximum growth performance, whereas the addition of L-Ile was not required. Experiment 9 indicated that feeding greater than 7.35% total Lys:CP decreased growth performance and Exp. 10 indicated that a SID Val:Lys ratio of 65% was sufficient for optimal growth of early nursery pigs. Implementing the results from the previous experiments, Exp. 11 determined that crystalline AA in nursery pigs diets can replace high amounts of fish meal, meat and bone meal, and poultry meal when balanced for minimum AA ratios and maximum Lys:CP with no negative effect on growth performance.
Keywords: Amino acids; Compensatory growth; Crystalline amino acids; Lysine; Pig; Animal Sciences (0475)